Designing User Interface & User Experience on Information System of Amil Zakat Institution Using Website-Based User Centered Design Method - Baharudin, Rismayada; Dauni, Popon; Purwadi, Purwadi (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
Amil Zakat Institution Yayasan Masyarakat Muslim Freeport Indonesian or better known as YMM FI is an institution that distributed to the community. However, even though it has been operating for a long time, YMM FI does not have a website as information media. The basis of good website is the existence of an attractive interface that is easily understood by users, therefore this study has designed a user interface and user experience using the user centered design method through its four stages, namely; the first stage is to understand the context of use, at this stage interviews are conducted with users, then the second stage specify user requirements is a description of the flow of the system that will run using a unified modelling language, then the third stage is the design solution at this stage the researcher has proposed a website interface design, then the last stage is evaluate against requirements. which is the evaluation stage of the proposed interface design. The evaluation stage is carried out to provide experience for users. Based on usability testing with pay attention to effective and efficient aspects. To get the value of the usability testing aspects, researchers used the cognitive walkthrough method and the system usability scale (SUS). In the effective aspect, an average value of 100% is obtained for the admin display and 96% for the muzakki display, then the effective aspect gets an average value of 100% for the admin display and 95% for the muzakki display, then the SUS average value is 76,5 almost close to 77 which gets a good grade.